The effects of BDNF rs6265 and FGF21 rs11665896 polymorphisms on alcohol use disorder-related impulsivity in Han Chinese adults - Yang, Shizhuo; Wang, Fan; Sun, Lanrong; Liu, Xinqian; Li, Siyuan; Chen, Yingjie; Chen, Lingling; Pan, Zeheng; Kang, Yimin; Chen, Yu-Hsin; Wang, Wei; Chen, Li; et al. (Frontiers in Psychiatry, 2024)
Introduction Patients with alcohol use disorder (AUD) often experience repeated withdrawal. Impulsivity is the most relevant factor influencing successful withdrawal. Brain-derived neurotrophic factor (BNDF) and fibroblast growth factor 21 (FGF21) are associated with impulsivity. Previous studies on the differential effects of BDNF or FGF21 on impulsivity have focused on single-gene effects and have inconsistent results. We aim to investigate the effects of BDNF rs6265 and FGF21 rs11665896, individually and together, on impulsivity during alcohol withdrawal in patients with AUD. Methods We recruited 482 adult Han Chinese males with AUD and assessed their impulsivity using the Barratt Impulsivity Scale. Genomic DNA was extracted and genotyped from peripheral blood samples. Statistical analysis was conducted on the data. Results The T-test and 2 × 2 analysis of variance were used to investigate the effects of the genes on impulsivity. There was a significant BDNF × FGF21 interaction on no-planning impulsiveness (F = 9.15, p = 0.003, η2p = 0.03). Simple main effects analyses and planned comparisons showed that BDNF rs6265 A allele × FGF21 rs11665896 T allele was associated with higher no-planning impulsiveness. Finally, hierarchical regression analyses revealed that only the interaction of BDNF and FGF21 accounted for a significant portion of the variance in no-planning impulsiveness. Conclusion and significance The combination of BDNF rs6265 A allele and FGF21 rs11665896 T allele may increase impulsivity and discourage alcohol withdrawal. Our study provides a possible genetic explanation for the effects of associated impulsivity in patients with AUD from the perspective of gene-gene interactions.